The role of the intestinal microbiome in antiphospholipid syndrome - van Mourik, Dagmar J. M.; Salet, Dorien M.; Middeldorp, Saskia; Nieuwdorp, Max; van Mens, Thijs E. (Frontiers in Immunology, 2022)
The antiphospholipid syndrome (APS) is a thrombotic autoimmune disease in which the origin of the disease-characterizing autoantibodies is unknown. Increased research effort into the role of the intestinal microbiome in autoimmunity has produced new insights in this field. This scoping review focusses on the gut microbiome in its relation to APS. EMBASE and MEDLINE were searched for original studies with relevance to the relation between the gut microbiome and APS. Thirty studies were included. Work on systemic lupus erythematosus, which strongly overlaps with APS, has shown that patients often display an altered gut microbiome composition, that the disease is transferable with the microbiome, and that microbiome manipulation affects disease activity in murine lupus models. The latter has also been shown for APS, although data on microbiome composition is less consistent. APS patients do display an altered intestinal IgA response. Evidence has accrued for molecular mimicry as an explanatory mechanism for these observations in APS and other autoimmune diseases. Specific gut microbes express proteins with homology to immunodominant APS autoantigens. The disease phenotype appears to be dependent on these mimicking proteins in an APS mouse model, and human APS B- and T-cells indeed cross-react with these mimics. Pre-clinical evidence furthermore suggests that diet may influence autoimmunity through the microbiome, as may microbial short chain fatty acid production, though this has not been studied in APS. Lastly, the microbiome has been shown to affect key drivers of thrombosis, and may thus affect APS severity through non-immunological mechanisms. Overall, these observations demonstrate the impact of the intestinal microbiome on autoimmunity and the importance of understanding its role in APS.